Peran Lingkungan Keluarga dan Sekolah dalam Pengembangan Bahasa Anak Usia Dini - Dermawan Dermawan; Syamsiah Depalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Language ability is a cornerstone in early childhood development, influencing almost every aspect of life, from social interaction to cognitive skills. A rich vocabulary, the ability to understand instructions, and clear self-expression are important indicators of successful language development. Language plays a very important role in helping children build relationships with others. The process of language acquisition is not something that happens naturally without stimulus, but is highly influenced by the environment where a child grows and develops. The two main environments that play a crucial role in shaping a child's language skills are the family and the school environment.